Ab initio study of the electronic and optical properties of Ag3AuS2 polymorphs. (23rd August 2017) - Shah, Syed Sarmad Ali; Khan, Afzal; Khan, Shah Haidar; Muhammad, Nisar; Khan, Saleem Ayaz; Ashiq, M Gulbahar; Murtaza, G
Abstract: Natural and synthetic uytenbogaardtite (Ag3 AuS2 ) polymorphs have been studied for their structural, compositional and thermodynamic properties. We investigated their electronic and optical properties for the first time using density functional theory. These calculations are based on the full potential linearized augmented plane wave method using the modified Becke–Johnson potential. Our calculations reveal that Ag3 AuS2 is a direct band gap semiconductor exhibiting three crystal phases, cubic, trigonal and triclinic. The calculated band gaps for cubic, trigonal and triclinic phases are 1.15, 2.15 and 1.73 eV, respectively. The band gaps of the Ag3 AuS2 polymorphs in the near infrared and visible region highlight the importance of these polymorphs for optoelectronic applications such as resistive switches, low-loss optical fibers, thin-film solar cells and thin-film photovoltaic devices. Furthermore, our calculations show that the electronic and optical properties of Ag3 AuS2 are crystal phase dependent.